Creating ‘safe-ish’ learning spaces—attempts to practice an ethics of care - Sykes, P.; Gachago, A. (South African Journal of Higher Education, 2018)
One way to approach the project of decolonising the university is to employ decolonising pedagogies, which allow the whole of people’s lived experience into teaching and learning spaces, affirm this experience as worthy of scholarly attention and create a dialogue between experience and theory. Encouraging the sharing of personal stories among diverse and differently positioned students however brings up questions about “safe spaces”. Using Tronto’s ethics of care as a normative framework we will reflect on a range of snapshot to exemplify ethical dilemmas encountered in a teacher education classroom within a digital storytelling project. Based on this analysis two main assumptions are challenged: that safe spaces exist and that safety is something that can be bestowed on students by the lecturer. We argue for teaching and learning that facilitates a heightened self-awareness on the part of (in particular white) educators about their own gendered, classed and raced subjectivities and how these play out in the classroom—a practice of care both towards others and towards the self. This self-awareness and self-care needs to be matched by the development of facilitation skills that may help to create learning spaces that re-affirm difference among learners while also enabling generative dialogue. We conclude with practical suggestions on how to implement such an attempt at practicing the ethics of care in the classroom.